A Teoria das Inteligências Múltiplas : Um Contributo para a Organização Curricular na Educação Pré-Escolar - Mestre, Amélia (2020)
The theory of Multiple Intelligences sees intelligence as flexible and not innate, and its development depends on the cultural environment in which individuals are inserted. According to this theory, there are, currently, nine types of intelligence that can be developed in individuals, however only the eight initials are approached, such as linguistic intelligence, logical-mathematical intelligence, spacial intelligence, musical intelligence, kinesthetic / bodily intelligence, naturalistic intelligence, interpersonal intelligence and, lastly, intrapersonal intelligence. This theory of psychology can be applied to curricular management of pre-school education, since it contemplates the individuality of each child, thus considering that not all children learn in the same way. According to this perspective, it’s necessary that educators know the learning profiles of each one and take them into account in pedagogical practice. Through the exhaustive analysis, it was possible to create a comparative conceptual framework that allows us to affirm that it’s possible to articulate the assumptions of this theory with the Orientações Curriculares para a Educação Pré-Escolar (OCEPE), since each intelligence corresponds to content areas, domains or subdomains provided in the state document guiding the educator's practice. In addition, the theory relates to the OCEPE, concerning the strategies to promote learning in children and the type of assessment to be undertaken, which should be complemented by observations and other types of data collection. Going further, is theoretically proven that the pedagogical models applied in Portugal can also be articulated with the theory of Multiple Intelligences, since some of the principles of the theory meet some objectives of the models, namely, with respect to (i) organization of the educational environment, (ii) implementation of projects, (iii) evaluation, (iv) documentation, among others. In this work, the aforementioned aspects are explored, resorting to a literature review that presupposes a documentary analysis and a content analysis.